A Study on the Social Perception of Risks From Electromagnetic Wave—Focusing on Big Data-Based Text Mining Analysis - Dong-Hun Kim; Beob-Heon Kim (SAGE Open)
This study aimed to analyze the social perceptions of risks and harm to the human body from electromagnetic waves, which have increased due to the era of the fourth Industrial Revolution and the development of information and communication technology (ICT), and to suggest alternatives. This study applied big-data-based text-mining analysis techniques to collect and analyze 10,681 Korean media reports and portal big data over the last 10 years. As a result, social perceptions shown in the media and portal big data recognized that national policies, such as THAAD, nearby facilities, electronic products used in daily life, and smartphone electromagnetic waves harm the human body and health. Therefore, to establish proper perceptions of electromagnetic waves, this study suggests policy implications, such as strengthening publicity activities for the public on electromagnetic wave safety, expanding the provision of relevant information on electronic products, and establishing a specialized organization for electromagnetic waves.